Formulation And Evaluation of Etoposide Nanosponges - Barish, Barish; S, Muthukumar.; Hurmathunnissa, Hurmathunnissa; Mathesh, K.; Mounesh, S.; Kumar, M.Sathish; G.M, Vallarasu.; P, Lavanya.; M, Gowsalya.; K, Sivasankar. (Journal of Neonatal Surgery, 2025)
The main objective of the study is to formulate Etoposide Nanosponges. The nanosponges were prepared by Emulsion solvent diffusion method using various concentrations of Eudragit and Ethyl cellulose. An ideal drug therapy attains effective drug concentration at the target site for a specified period of time and minimizes general and local side effects. To obtain a desirable therapeutic response, the correct amount of drug should be transported and delivered to the site of action with subsequent control of drug release.Nanosponges are made of microscopic particles with few nanometers wide cavities, in which a large variety of substances can be encapsulated. These particles possess the ability to carry both lipophilic and hydrophilic substances and thereby improving the solubility of poorly water soluble molecules. The prepared nanosponges were evaluated for particle size, zeta potential, entrapment efficiency and in vitrodrug release. The prepared nanosponges using Ethyl Cellulose an Eudragit have the average particle size was found to be 192.6 nm and 100.81nm which are lesser than 5µm, zeta potential was found to be -15.2mV and -23.4mV respectively. The formulatedEtoposide nanospongescanbeused inthetreatment ofcancersuchasleukemiaandothercancers.This canbe targeted to the cancerous cells and produce sustained drug delivery which in turn reduces the dose, frequency of administration and the side effects.